EXPLORING MODEL OF TEACHING USED BY THE LECTURERS AT THE FIFTH SEMESTER OF ENGLISH EDUCATION DEPARTMENT - Arinda Nurul Widyaningrum; Muhammad Yaumi (Universitas islam Negeri Alauddin Makassar, 2021)
The lecturer is one of the needs in the educational process. In carrying out the professionalism, they should prepare appropriate model of teaching to support learner’s achievement. This study sought to explore how the lecturer in English Education Department prepare and implement their model of teaching and what students’ perception. It utilized a phenomenological design inquiry with a qualitative approach. Participants in this research were lecturers and students. They were taken purposively. The data were collected through an observations sheet, interview guide, focus group discussion, and document study. The observation, interview, and document study were done to the lecturers, and the focus group discussion was done to the students. As a result, three lecturers of the English Education Department used a different model of teaching. The first lecturer used the cooperative learning model, the second lecturer used the multi skill strategy, and the third lecturer used the blended learning model. Besides, students had various perception of each model of teaching was implemented by the lecturer. They shared the positive and negative perception.